Circadian preference is associated with multiple domains of trait and state level impulsivity. (3rd June 2022) - Hasler, Brant P.; Wallace, Meredith L.; Graves, Jessica L.; Molina, Brooke S. G.; Pedersen, Sarah L.
ABSTRACT: Impulsivity is a multidimensional construct with well-documented risk for substance use problems at both the trait- and state levels. A circadian preference towards eveningness has been linked to trait-level, global impulsivity, but whether this association holds true across multiple dimensions of impulsivity and whether actual sleep timing shows parallel associations with impulsivity remain unclear. Here, we extend existing literature by investigating whether eveningness is associated with multiple facets of both trait- and state-level impulsivity. We also examined these associations utilizing daily measures of sleep timing and duration and explored whether they differed by sex and/or race. All participants were moderate-to-heavy social drinkers aged 21–35. Primary analyses included 78 participants (100% White male participants: Sample 1) with circadian preference data (Composite Scale of Morningness: CSM) and sleep timing (midsleep) and duration assessed via daily self-report over 10 days. Five facets of impulsivity were assessed via the UPPS-P, both at baseline (full scale; trait-level) and up to 6 times per day over 10 days (reduced scale; state-level). Linear regression and mixed-effects models were used to examine between- and within-person associations of impulsivity with measures of circadian preference, timing, and duration, accounting for covariates. Exploratory analyses combined Sample 1 with an additional more diverse sample (Sample 2), resulting in a total of 182 participants (29.1% self-identified as Black, 29.7% as female) with daily self-report sleep timing and duration only (no circadian preference). Primary between-person models found that eveningness was associated with multiple facets of impulsivity, at trait (lack of perseverance) and state levels (negative and positive urgency, lack of perseverance, and lack of premeditation), while average midsleep and duration were generally unrelated to impulsivity. Primary within-person models largely paralleled the between-person findings. Exploratory analyses in the larger combined Samples 1 and 2 (without circadian preference) found that later midsleep timing was associated with greater mean state-level impulsivity across multiple facets, associations that may differ by race and sex. In a sample of White male participants, circadian preference for eveningness was strongly associated with multiple facets of impulsivity, at both trait- and state-levels, which may contribute to risk for substance use. Preliminary findings suggest sex and race differences in sleep-impulsivity associations, but future research with objective sleep/circadian measures in larger, more diverse samples will be important to clarify implications for sleep-focused prevention and/or treatment of substance use.